1998
DOI: 10.1016/s0006-3495(98)77709-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrophobicity and Solvent-Mediated Charge-Charge Interactions in Stabilizing α-Helices

Abstract: A theoretical study to identify the conformational preferences of lysine-based oligopeptides has been carried out. The solvation free energy and free energy of ionization of the oligopeptides have been calculated by using a fast multigrid boundary element method that considers the coupling between the conformation of the molecule and the ionization equilibria explicitly, at a given pH value. It has been found experimentally that isolated alanine and lysine residues have somewhat small intrinsic helix-forming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 65 publications
6
38
0
Order By: Relevance
“…as well as entropic contributions (the difference between the Ala and Gly propensities can be explained by a large reduction in conformational space available when the side-chain H of a glycine is replaced by a CH3 in Ala) (54)(55)(56)(57)(58). Many of these effects can be accounted for by a semiempirical free energy of solvation (59).…”
Section: Resultsmentioning
confidence: 99%
“…as well as entropic contributions (the difference between the Ala and Gly propensities can be explained by a large reduction in conformational space available when the side-chain H of a glycine is replaced by a CH3 in Ala) (54)(55)(56)(57)(58). Many of these effects can be accounted for by a semiempirical free energy of solvation (59).…”
Section: Resultsmentioning
confidence: 99%
“…This is also observed in experiments on many heterogeneous peptides that can be folded into alternative stable structures by changing the solution conditions such as the pH, salt, or organic cosolvent concentration; peptide concentration; and the redox state (Rosenheck and Doty 1961;Kabsch and Sander 1984;Mutter and Hersperger 1990;Mutter et al 1991;Reed and Kinzel 1991;Zhong and Johnson 1992;Cohen et al 1993;Dado and Gellman 1993;Waterhous and Johnson 1994;Cerpa et al 1996;Fukushima 1996;Schenck et al 1996;Zhang and Rich 1997;Tuchscherer et al 1999;Awasthi et al 2001;Wildman et al 2002). Although there are many computer simulation studies in which the transition between ␣-helix and random coil of polyalanines is observed (Okamoto and Hansmann 1995;Vila et al 1998;Hansmann and Okamoto 1999;Alves and Hansmann 2000;Mitsutake and Okamoto 2000;Alves and Hansmann 2001;Garcia and Sanbonmatsu 2002;Olivella et al 2002;Peng and Hansmann 2002;Ghosh et al 2003;Ohkubo and Brooks III 2003;Peng et al 2003), there are only two studies thus far that predict the formation of both ␣-helix and ␤-structures (Levy et al 2001;Ding et al 2003). The vast majority of simulation studies by other investigators mentioned here are based on all-atom models, which prevents them from exploring transitions between different peptide structures over a wide range of solvent conditions and temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…At low PS-20/ darbepoetin alfa (<1.5), the binding may only cause hydration changes to local regions of the protein, increasing the observed relative helicity. [63][64][65][66][67] As the PS-20/darbepoetin alfa (>1.5) increases, PS-20 binding could start to partially unfold the protein, causing the Trp to become more hydrated (lower quantum yield) and causing the decrease in relative helicity. In contrast, PS-80 binds to protein without unfolding the protein over a broader range of PS-80/darbepoetin alfa.…”
Section: Discussionmentioning
confidence: 99%